Vocabulary in autism spectrum disorders. Part 1: Research directions, areas and methods - Hrycyna, Ewa (Logopedia Silesiana, 2021)
This article is the first part of a study concerned with vocabulary in autism spectrum disorders. In a brief historical outline, Ewa Hrycyna describes the main directions of the research on autism and their relation to linguistic issues, including lexical ones. She then goes on to look at the main areas of the research on vocabulary in autism. Her examination takes into account both the quantitative and qualitative aspects. The latter, particularly significant for autism, is revealed at the level of expression and understanding, and concerns the vocabulary content and the depth of semantic understanding. In the final section of her article, the author identifies the main problems of the methodology which has dominated autism research so far.